2015
DOI: 10.1074/jbc.m114.619353
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Activities of Protein Disulfide Isomerase (PDI) and PDIA3 Protein, a Role of the Bcl-2 Protein Bak

Abstract: Background: Protein disulfide isomerase (PDI) family members are chaperones involved in apoptotic signaling through unclear mechanisms. Results: Pharmacological inhibition of PDI and PDIA3 activities reduces apoptotic signaling. Purified PDI and PDIA3 proteins induce Bak-dependent mitochondrial outer membrane permeabilization in vitro. Conclusion: PDI and PDIA3 possess proapoptotic function through inducing Bak oligomerization. Significance: The data show a novel mechanism of PDI/PDIA3-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 48 publications
2
56
0
Order By: Relevance
“…ER stress mediated induction of ERp57 leads to interaction with Bak and forms disulfide (-S-S-) mediated Bak oligomerization, promoting intrinsic apoptosis 11, 15, 19 . Therefore, we next determined whether ERp57 deletion in mice decreases HDM-induced -S-S- mediated oligomerization of Bak and activation of caspase-3 (apoptotic marker).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ER stress mediated induction of ERp57 leads to interaction with Bak and forms disulfide (-S-S-) mediated Bak oligomerization, promoting intrinsic apoptosis 11, 15, 19 . Therefore, we next determined whether ERp57 deletion in mice decreases HDM-induced -S-S- mediated oligomerization of Bak and activation of caspase-3 (apoptotic marker).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on ER stress-mediated apoptosis have also shown involvement of ERp57 in disulfide-mediated oligomerization of proapoptotic Bak on the ER and mitochondria associated membranes 11, 15, 19, 33 . Based on the results presented herein indicating that ERp57 deleted mice showed decreased oligomerization of Bak and apoptosis marker active caspase-3, it is reasonable to speculate that ERp57 could be regulating apoptosis of epithelial cells during HDM challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotic cells, the endoplasmic reticulum stress induces up-regulation of enzymes such as PDI to prevent the aggregation of malformed proteins [61]. Zhao and co-workers have shown that the PDI overexpression induces mitochondrial membrane permeabilization generating a proapoptotic signal [62]. It was also possible to identify differential regulation of proteins that have been associated with 7KC in the literature, such as heat shock proteins (hsp90 and hsp70).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Ero1L-1␣ is an ER-associated protein that oxidizes PDI, which can directly catalyze the formation of disulfide bonds in folding proteins (44). The members of the PDI family of proteins act as enzymatic chaperones in the ER for misfolded proteins and can mediate apoptosis signaling through a Bak-dependent proapoptotic function (45). In the absence of Asyn expression, the activation of specific ER stress pathways identified in this system would be expected to support viral growth, support viral replication, and modulate apoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%